Prevention, diagnosis and treatment of the neonatal sepsis: Clinical practice guideline-based evidence in a peruvian institute specialized - Dávila Aliaga, Carmen (2020)
Introduction. Neonatal sepsis is a set of clinical signs and symptoms caused by a systemic infection, associated with maternal, neonatal or hospital risk factors. Objective. Provide informed recommendations for the best available evidence for the prevention, diagnosis and treatment of neonatal sepsis. Methods an Evidence-based Clinical Practice Guide (CPG) was developed through an adaptation process, in charge of a team of methodologists and neonatologists who are experts in the clinical management of neonatal sepsis. The search and pre-selection of CPGs that respond to the scope and objectives set were carried out, using the AGREE-II instrument, the methodological quality of the guides was evaluated and their adaptation decided. To identify the evidence that answers the questions in the guideline, a systematic search was carried out in multiple databases: Medline / PubMed, Embase / Ovid, Cochrane Library and LILACS. These were selected and critically analyzed by clinical and methodological peers, the recommendations were elaborated using the GRADE approach. Results. 16 clinical questions and recommendations based on evidence were formulated, which were reached, through a deliberative dialogue of clinical experts from different reference hospitals for the management of neonatal sepsis in Peru. The recommendations address the identification of risk factors, the use of confirmatory methods and antibiotic treatment as prophylaxis and during disease management. Conclusions. The CPG allows standardizing the clinical management of neonatal sepsis, as well as the identification of research needs to be carried out in the Peruvian context.